+0

# If we express 3x^2-6x-2 in the form a(x-h)^2+k what is a+h+k

+1
417
4
+1442

If we express 3x^2-6x-2 in the form a(x-h)^2+k what is a+h+k

Thanks this one confused me

Oct 22, 2017

#1
+27544
+1

Same process as for https://web2.0calc.com/questions/the-quadratic-x-2-20x-36-can-be-written-in-the-form, except you now compare the coefficient of the x^2 term as well.

a(x - h)^2 + k → a(x^2 - 2hx + h^2) + k → ax^2 - 2ahx + ah^2 +k

coeff of x^2:   a = 3

coeff of x:      -2ah = -6

constant;      ah^2 + k = -2

I'll leave you to complete it!

Oct 22, 2017
edited by Alan  Oct 22, 2017
#2
+1442
+2

So the answer would be -7?

AnonymousConfusedGuy  Oct 22, 2017
#3
+1442
+2

no -7 didn't work can you tell me how to complete it please?

Oct 22, 2017
#4
+27544
+1

Well, we have:

coeff of x^2:   a = 3

coeff of x:      -2ah = -6  → -2*3*h = -6  → 6h = 6  →  h = 1

constant;      ah^2 + k = -2 →  3*(1^2) + k = -2  →  3 + k = -2  →  k = -5

Hence  a + h + k = 3 + 1 - 5  or  a + h + k = -1

Alan  Oct 22, 2017